PENGARUH KEPRIBADIAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. OCEAN INDUSTRI - Permata, Nuniek; Saputra, Saripudin; Diantoro, Eman; Alamsyah, Alamsyah (Gapenas Publisher, 2024)
Performance has a very important meaning in a company to achieve large profits because it can make a large contribution to company profits. The better a person's performance in the company, the more profits the company will receive. Of the many factors that influence employee performance, one of them is the employee's own personality and job satisfaction.The purpose of this research is to determine the influence of personality on employee performance at PT Ocean Industry, to determine the influence of job satisfaction on employee performance at PT Ocean Industry, to determine the simultaneous influence of personality and job satisfaction on employee performance at PT Ocean Industry.The method used in this research is a quantitative method. The variables in this research consist of the dependent variable, namely employee performance, while the independent variables are personality and job satisfaction. The population in this research is 800 production employees at PT. Ocean Industry with a sample size of 90 employees.He results of the research show that based on the results of the t test the personality variable obtained a t_count value of 5,477 > t_tabel (1.662), the results of the t test for the job satisfaction variable obtained a t_count value (12,510) > t_tabel (1.662) and the F test results obtained an F_count value of 87,416 > F_tabel ( 3.95).The conclusion of this research is that personality influences employee performance, job satisfaction influences employee performance, simultaneously personality and job satisfaction influence employee performance. The percentage of employee performance variables that can be explained by the independent variables is shown by the R Square value, which is 0.668. It can be concluded that the magnitude of the influence of personality and satisfaction on employee performance is 66.8%, while the remaining 33.2% is explained by other variables not examined in this research